2002
DOI: 10.1523/jneurosci.22-11-04372.2002
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Neurotransmitter Release by Synapsin III

Abstract: Synapsin III is the most recently identified member of the synapsin family, a group of synaptic vesicle proteins that play essential roles in neurotransmitter release and neurite outgrowth. Here, through the generation and analysis of synapsin III knock-out mice, we demonstrate that synapsin III regulates neurotransmitter release in a manner that is distinct from that of synapsin I or synapsin II. In mice lacking synapsin III, the size of the recycling pool of synaptic vesicles was increased, and synaptic depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
154
1
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 142 publications
(163 citation statements)
references
References 39 publications
6
154
1
2
Order By: Relevance
“…The somewhat contrasting locomotor responses to amphetamine and methylphenidate in the CK1δ OE mice might indicate that the overexpression of CK1δ affects especially the presynaptic machinery to modulate neurotransmitter release. It is well established that protein phosphorylation can modulate neurotransmitter release (30,31). It has been found that purified synaptic vesicles from rat brain were highly enriched in CK1.…”
Section: Discussionmentioning
confidence: 99%
“…The somewhat contrasting locomotor responses to amphetamine and methylphenidate in the CK1δ OE mice might indicate that the overexpression of CK1δ affects especially the presynaptic machinery to modulate neurotransmitter release. It is well established that protein phosphorylation can modulate neurotransmitter release (30,31). It has been found that purified synaptic vesicles from rat brain were highly enriched in CK1.…”
Section: Discussionmentioning
confidence: 99%
“…Newborn pups (postnatal day 0) were genotyped by PCR and then killed to prepare hippocampal neurons, as described by Gitler et al (2004). Microisland cultures of hippocampal neurons were prepared as described previously (Bekkers and Stevens, 1991;Feng et al, 2002), with the addition of glia feeder cells to support neuronal survival. Neurons were allowed to mature for 9 -13 d before being used for electrophysiological recordings.…”
Section: Methodsmentioning
confidence: 99%
“…Glutamate and GABA presynaptic terminals also differ in their adaptive response to strong depolarization (Moulder et al, 2004). In other examples, different isoforms of vesicle and active zone proteins govern vesicle availability at glutamate and GABA synapses (Feng et al, 2002;Varoqueaux et al, 2002;Gitler et al, 2004). The subtype(s) of Ca 2ϩ channel driving release can differ between glutamate and GABA synapses, with most glutamate release controlled by a combination of P/Q-and N-type calcium channels (Luebke et al, 1993;Reid et al, 1997;Wu and Borst, 1999;Cao et al, 2004) and many GABA synapses governed by a single class of Ca 2ϩ channel (Poncer et al, 1997;Brager et al, 2003).…”
Section: Introductionmentioning
confidence: 99%